Electrical Power Distribution System modeling with VHDL-AMS for the construction of a Real-Time Digital Simulator using FPGAS devices - Ibarra Hernandez, Frank Alberto [UNESP] (2012)
This paper presents a distribution feeder simulation using VHDL-AMS, considering the standard IEEE 13 node test feeder admitted as an example. In an electronic spreadsheet all calculations are performed in order to develop the modeling in VHDL-AMS. The simulation results are compared in relation to the results from the well knowing MatLab/Simulink environment, in order to verify the feasibility of the VHDL-AMS modeling for a standard electrical distribution feeder, using the software SystemVision™. This paper aims to present the first major developments for a future Real-Time Digital Simulator applied to Electrical Power Distribution Systems. © 2012 IEEE.